Use frequency of traditional Chinese medicine in Taiwan - Chen Yu-Chun; Kung Yen-Ying; Chen Tzeng-Ji; Chen Fang-Pey; Chou Li-Fang; Chen Fan-Jou; Hwang Shinn-Jang (BMC, 2007)
Abstract Background Use of Traditional Chinese medicine (TCM), an important category of complementary and alternative medicine (CAM), has increased substantially in Western countries during the past decade. Use of TCM is also widespread in the Chinese population. However, few informative data have been obtained to date by large-scale investigations of TCM use in the Chinese population. This study was aimed at elucidating the demographics and patterns of TCM use in Taiwan. Methods We employed the complete datasets of TCM outpatient reimbursement claims from 1996 to 2001, including the use of Chinese herbal remedies, acupuncture and traumatology manipulative therapy, to analyse use frequencies, the characteristics of TCM users, and the disease categories that were treated by TCM in Taiwan. Results At the end of 2001, 6,142,829 (28.4%) among the 21,653,555 valid beneficiaries of the National Health Insurance in Taiwan had used TCM during the year. However, 13,536,266 subjects (62.5%) had used TCM at least once during the whole 6-year period from 1996 to 2001, with a total of 156,224,266 visits (mean 11.5 visits per user). The mean number of TCM users per annum was 5,733,602, with a mean increment of 1,671,476 (29.2%) of new users yearly. Among TCM users, female was higher than male (female:male = 1.13:1), and the age distribution displayed a peak at around the 30s, followed by the 20s and 40s. Chinese herbal remedies (85.9%) were the most common TCM modality used by this population, followed by acupuncture (11.0%) and traumatology manipulative therapies (3.1%). Private TCM clinics provided most of the TCM care (82.6%), followed by private TCM hospitals (12.0%). The top ten major disease categories for TCM visits were diseases of the respiratory system, musculoskeletal system and connective tissue; symptoms, signs and ill-defined conditions; injury and poisoning; diseases of the digestive system, genitourinary system, skin and subcutaneous tissue, nervous system and sense organs, circulatory and endocrine system; nutritional and metabolic diseases; and immunological disorders. Conclusion TCM was popular among the Chinese population in Taiwan during the period studied. More than 60% of all subjects had used TCM during the 6-year interval. TCM was widely used by the Chinese population to treat problems and diseases of major human organ systems recognised by western medicine. This study provides information about the use frequencies of TCM and the disease categories treated by TCM, which should be useful for health policy makers and for those considering the integration of TCM and Western medicine.